Resurgence of global populism a psychoanalytic study of projective identification, blame-shifting and the corruption of democracy - Messina, Karyne E. (Routledge, Taylor & Francis Group, 2023)
"Resurgence of Global Populism provides a psychoanalytic perspective to the global implications of the populist movement in the U.S. and its relationship to other parts of the world, particularly focusing on the presidency and legacy of Donald Trump. The book explores Trump's use of psychological form of manipulation known as projective identification and how his use of this defense mechanism has influenced global institutions, political discourse, and quality of life in the long term. Messina explores the correlation between Trump's rhetoric and an increase in reported racism and prejudiced violence worldwide, disintegration of global values, and a radicalized political climate. She analyzes the dynamics between Trump and his supporters, political opponents, and successors, considers the COVID-19 pandemic as a study of Trump's views of the world, and considers the roles of social and television media. The book concludes with an explanation of antidotes to projective identification, including thoughtful debate and meaningful discussions and scripted dialogues for global healing. This insightful book will be of interest to psychoanalysts and psychotherapists, academics and students of political psychology and political movements, and readers interested in a deeper analysis of populism and political dynamics"--